2006
DOI: 10.1021/jp056240o
|View full text |Cite
|
Sign up to set email alerts
|

Modified Lithium Borohydrides for Reversible Hydrogen Storage

Abstract: In an attempt to develop lithium borohydrides as reversible hydrogen storage materials with high hydrogen storage capacities, the feasibility of reducing the dehydrogenation temperature of the lithium borohydride and moderating rehydrogenation conditions was explored. The lithium borohydride was modified by ball milling with metal oxides and metal chlorides as additives. The modified lithium borohydrides released 9 wt % hydrogen starting from 473 K. The dehydrided modified lithium borohydrides absorbed 7-9 wt … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
197
0
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 203 publications
(210 citation statements)
references
References 6 publications
10
197
0
1
Order By: Relevance
“…Ni phases are also observed after heating to 330°C, and no additional peaks corresponding to the Mg 2 Ni phase were observed, indicating that the enhancement of the first-step dehydrogenation can be attributed to the catalytic effect of nano-Ni, which is highly active in decreasing the activation energy of MgH 2 for hydrogen desorption by surface activation, as reported previously. 29 On further heating to 500°C, LiBH 4 disappeared and LiH phase was observed, indicating that the system is fully dehydrogenated at 500°C, as the boron phase in dehydrogenated samples of LiBH 4 -relevant samples is usually amorphous, 22 agreeing well with the TPD results ( Fig. 1).…”
Section: Resultssupporting
confidence: 82%
See 2 more Smart Citations
“…Ni phases are also observed after heating to 330°C, and no additional peaks corresponding to the Mg 2 Ni phase were observed, indicating that the enhancement of the first-step dehydrogenation can be attributed to the catalytic effect of nano-Ni, which is highly active in decreasing the activation energy of MgH 2 for hydrogen desorption by surface activation, as reported previously. 29 On further heating to 500°C, LiBH 4 disappeared and LiH phase was observed, indicating that the system is fully dehydrogenated at 500°C, as the boron phase in dehydrogenated samples of LiBH 4 -relevant samples is usually amorphous, 22 agreeing well with the TPD results ( Fig. 1).…”
Section: Resultssupporting
confidence: 82%
“…As is known, the boron phase in the dehydrogenated samples of LiBH 4 -relevant is usually amorphous and therefore can not be detected by means of XRD. 22 Similar products corresponding to Mg or Li-Mg, as well as some LiH and MgB 2 were also identified in 2LiBH 4 -MgH 2 sample after dehydrogenated at 500°C. The observed MgH 2 phase in the dehydrogenated state of 2LiBH 4 -MgH 2 or 2LiBH 4 -MgH 2 -0.05Ni sample is probably from the hydrogenation of Mg or Li-Mg during the temperature of 500°C cooling down to room temperature because about 1 bar hydrogen pressure was observed in the vessel after dehydrogenated at 500°C.…”
Section: Resultsmentioning
confidence: 62%
See 1 more Smart Citation
“…11 However later research showed that SiO 2 reacts with LiBH 4 to form stable silicates 23,24 while irreversibly releasing hydrogen, as is the case with most metal oxide additives. 25,26 A large range of materials, including metal halides, 12,14,27 Al, Pt, carbon nanotubes, fullerene and Ni, 13,[15][16][17]28 has been investigated in an effort to identify an effective catalyst for LiBH 4 de/rehydrogenation. Addition of these materials generally led to a decrease in the dehydrogenation temperatures but most of the systems still required temperatures above 400 C and hydrogen pressures above 40 bar for only achieving partial rehydrogenation of the desorbed material.…”
Section: Introductionmentioning
confidence: 99%
“…In view of their high theoretical hydrogen storage capacities, metal borohydrides have recently been the subject of intensive investigation. [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] The dehydrogenation of lithium and Group II borohydrides is plagued by severe kinetic limitations and irreversibility that precludes the utilization of these compounds under practical conditions, [2][3][4][5][6][7][8][9][10] even as components of binary hydride mixtures. [12][13][14][15][16][17][18] Many transition metal borohydride complexes also have suitable gravimetric hydrogen densities.…”
Section: Introductionmentioning
confidence: 99%